3D genome architecture from populations to single cells. (April 2015) - Furlan-Magaril, Mayra; Várnai, Csilla; Nagano, Takashi; Fraser, Peter
Abstract : Dominated by microscopy for decades the nuclear genome organization field has recently undergone a dramatic transition fuelled by new next generation sequencing technologies that are beginning to bridge the gap between microscopic observations and molecular scale studies. It is no longer in doubt that the nucleus is spatially compartmentalized and that the genome organization with respect to these compartments is cell type specific. However, it is still unclear if and how this organization contributes to genome function, or whether it is simply a consequence of it. This uncertainty is partly due to the cell-to-cell variability of genome organization, but also due to limitations of the measurement techniques and the scale of the problem at hand. Here we discuss some of the exciting recent progress made towards understanding three-dimensional genome architecture and function.